Neurogenic substance P-influences on action potential production in afferent neurons of the kidney? - Rodionova, Kristina; Hilgers, Karl Friedrich; Linz, Peter; Schaetzl, Johannes; Raschke, Giulia; Ott, Christian; Schmieder, Roland; Schiffer, Mario; Amann, Kerstin Ute; Veelken, Roland; Ditting, Tilmann (Pflügers Archiv: European Journal of Physiology, 2021)
We recently showed that a substance P (SP)-dependent sympatho-inhibitory mechanism via afferent renal nerves is impaired in mesangioproliferative nephritis. Therefore, we tested the hypothesis that SP released from renal afferents inhibits the action potential (AP) production in their dorsal root ganglion (DRG) neurons. Cultured DRG neurons (Th11-L2) were investigated in current clamp mode to assess AP generation during both TRPV1 stimulation by protons (pH 6) and current injections with and without exposure to SP (0.5 mu mol) or CGRP (0.5 mu mol). Neurons were classified as tonic (sustained AP generation) or phasic (<= 4 APs) upon current injection; voltage clamp experiments were performed for the investigation of TRPV1-mediated inward currents due to proton stimulation. Superfusion of renal neurons with protons and SP increased the number of action potentials in tonic neurons (9.6 +/- 5 APs/10 s vs. 16.9 +/- 6.1 APs/10 s, P < 0.05, mean +/- SD, n = 7), while current injections with SP decreased it (15.2 +/- 6 APs/600 ms vs. 10.2 +/- 8 APs/600 ms, P < 0.05, mean +/- SD, n = 29). Addition of SP significantly reduced acid-induced TRPV1-mediated currents in renal tonic neurons (- 518 +/- 743 pA due to pH 6 superfusion vs. - 82 +/- 50 pA due to pH 6 with SP superfusion). In conclusion, SP increased action potential production via a TRPV1-dependent mechanism in acid-sensitive renal neurons. On the other hand, current injection in the presence of SP led to decreased action potential production. Thus, the peptide SP modulates signaling pathways in renal neurons in an unexpected manner leading to both stimulation and inhibition of renal neuronal activity in different (e.g., acidic) environmental contexts.
CRIS-Team WoS Importer:2021-04-16